Coupled atomistic spin-lattice simulations of ultrafast demagnetization in 3d ferromagnets - M. Pankratova; I. P. Miranda; D. Thonig; M. Pereiro; E. Sjöqvist; A. Delin; P. Scheid; O. Eriksson; A. Bergman (Scientific Reports, 2024)
Abstract Despite decades of research, the role of the lattice and its coupling to the magnetisation during ultrafast demagnetisation processes is still not fully understood. Here we report on studies of both explicit and implicit lattice effects on laser induced ultrafast demagnetisation of bcc Fe and fcc Co. We do this using atomistic spin- and lattice dynamics simulations following a heat-conserving three-temperature model. We show that this type of Langevin-based simulation is able to reproduce observed trends of the ultrafast magnetization dynamics of fcc Co and bcc Fe. The parameters used in our models are all obtained from electronic structure theory, with the exception of the lattice dynamics damping term, where a range of parameters were investigated. It was found that while the explicit spin-lattice coupling in the studied systems does not impact the demagnetisation process notably, the lattice damping has a large influence on the details of the magnetization dynamics. The dynamics of Fe and Co following the absorption of a femtosecond laser pulse are compared with previous results for Ni and similarities and differences in the materials’ behavior are analysed. For all elements investigated so far with this model, we obtain a linear relationship between the value of the maximally demagnetized state and the fluence of the laser pulse , which is in agreement with experiments. Moreover, we demonstrate that the demagnetization amplitude is largest for Ni and smallest for Co. This holds over a wide range of the reported electron-phonon couplings, and this demagnetization trend is in agreement with recent experiments.